2021
DOI: 10.1007/s00170-021-07113-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of process parameters for sheet lamination based on laser micro-spot welding of austenitic stainless steel sheets for bone tissue applications

Abstract: The laser micro-spot welding process was studied to implement a sheet lamination process-based methodology for the fabrication of austenitic stainless steel scaffolds. AISI 302 sheets with a thickness of 254 μm were laser cut and laser welded. Experimental tests were carried out with different values of average laser power (i.e., 180, 200, and 220 W) and different exposure times (25, 50, 75, 100, 125 ms). The micro-spot welds were visually inspected according to the ISO 13919-1 Class B requirements. Spot welds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…These results demonstrate high repeatability in the micro-spot weld dimensions obtained in this works. Additionally, it is observed that the micro-spot welds under the Z height of 2 mm presented a fluted shape which is consistent with our previous study [ 10 ]. After the Z height of 2 mm, the micro-spot welds showed a parabolic shape; this change in the weld beads indicated a difference in the heat transfer phenomena [ 10 , 31 ] resulting from the stacking process.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…These results demonstrate high repeatability in the micro-spot weld dimensions obtained in this works. Additionally, it is observed that the micro-spot welds under the Z height of 2 mm presented a fluted shape which is consistent with our previous study [ 10 ]. After the Z height of 2 mm, the micro-spot welds showed a parabolic shape; this change in the weld beads indicated a difference in the heat transfer phenomena [ 10 , 31 ] resulting from the stacking process.…”
Section: Resultssupporting
confidence: 92%
“…Forty-three sheets were stacked using laser micro-spot welding. The scaffold was joined using the methodology explained in our previous work [ 10 ]. The final scaffold was cut from the stack using a wire electrical discharge machining (WEDM) machine.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations